TEMPERATURE-INDEPENDENT SOURCE OF REFERENCE VOLTAGE FOR INTEGRATED MICROCIRCUITS WITH LOW SUPPLY VOLTAGE - TSYMBAL, OLEKSANDR; KORNIEV, VOLODYMYR; BONDARENKO, VIKTOR (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The principles of developing reference voltage sources (RVS) of integrated microcircuits and ways of achieving their temperature independence are considered. The existing problem of implementing a high-quality voltage source for modern microcircuits operating with a supply voltage below 1 V, the demand for which is growing rapidly recently, is noted. A typical circuit of the reference voltage source, whose temperature independence is based on the cumulative effect of using units with opposite temperature dependence, has been analyzed. Advantages and disadvantages of existing architectural solutions of reference voltage sources are considered. It is shown that the reason for the instability and nonlinearity of the output reference voltage at low values of the supply voltage is that the principle of operation of these RVSs is based on the properties of the p-n junction of the semiconductor, and depends on its so-called band gap, which for silicon is 1.25V. The temperature dependence of one "shoulder" of the RVS can be compensated by the opposite temperature dependence of the second "shoulder". But at low voltages, nonlinearities of higher orders become noticeable, which negatively affects the quality of the resulting output voltage. Another architectural solution for developing a reference voltage source using two RVSs implemented on parasitic p-n-p and n-p-n bipolar transistors, which are present in any CMOS technology, with subsequent subtraction of the generated currents using current mirrors, is proposed. As a result, it is possible to obtain a temperature-independent resulting current, and the output reference voltage released on the output resistor will have a low temperature dependence, due only to the temperature dependence of the resistance of the output resistor. In this way, it is possible to obtain a reference voltage source with low temperature dependence, capable of operating at a supply voltage equal to or below 1 V. This solution has the possibility of implementation in the standard CMOS technology of manufacturing integrated circuits. Ways for further improvement of the system are suggested.